Is Recovery Faster for Mobile-bearing Unicompartmental than Total Knee Arthroplasty? - Lombardi, Adolph V. (Springer-Verlag, 2009)
How does unicompartmental compare with total knee arthroplasty in durability, incidence of complications and manipulations, recovery, postoperative function, and return to sport and work? We matched 103 patients (115 knees) treated with a mobile-bearing unicompartmental device through July 2005 to a selected group of 103 patients (115 knees) treated with cruciate retaining total knee arthroplasty for bilaterality, age, gender and body mass index. Patients who underwent a unicompartmental surgery had better range of motion at discharge and shorter hospital stay than those who had a total knee arthroplasty (77° versus 67° and 1.4 versus 2.2 days). At 6 weeks, Knee Society functional scores and range of motion were higher for unicompartmental than total knees (63 versus 55 and 115° versus 110°). Patient-perceived Oxford scores were similar between groups (unicompartmental 5.4 versus total 4.1). Average times to return to work and sport were similar for both groups. Minimally invasive unicompartmental knee arthroplasty demonstrated better early ROM, shorter hospital stays, and improved functional scores. No advantage was seen in terms of return to work, return to sport, or Oxford scores. The data suggest minimally invasive unicompartmental arthroplasty using a rapid recovery protocol allows patients a faster return to a more functional level than total knee arthroplasty. Level of Evidence: Level III, therapeutic study. See the guidelines online for a complete description of level of evidence.